Quality of life, anxiety and depression in patients with chronic obstructive pulmonary disease - Lima,César de Andrade de (2020)
ABSTRACT Objective: to assess quality of life, anxiety and depression in patients with Chronic Obstructive Pulmonary Disease. Method: a cross-sectional, quantitative study, conducted in a reference hospital for the treatment of pulmonary diseases. Seventy patients were assessed, using a sociodemographic and clinical questionnaire, Beck’s anxiety and Depression Inventories and the SF-36 Quality of Life Scale. Results: the participants had better quality of life in the vitality, mental health and social role functioning domains (median=50.0) and worse in limitation by physical and emotional role functioning (median=0.0 points). Anxiety, depression and oxygen dependence were associated with poorer results in the quality of life domains. Conclusion: all patients were classified with severe anxiety level and moderate depression predominance. Patients had low quality of life scores in all domains.